Safety profile of baricitinib for the treatment of rheumatoid arthritis over a median of 3 years of treatment: an updated integrated safety analysis. (June 2020) - Genovese, Mark C; Smolen, Josef S; Takeuchi, Tsutomu; Burmester, Gerd; Brinker, Dennis; Rooney, Terence P; Zhong, Jinglin; Daojun, Mo; Saifan, Chadi; Cardoso, Anabela; Issa, Maher; Wu, Wen-Shuo; et al.
Summary: Background: Baricitinib is an oral selective inhibitor of Janus kinase (JAK) 1 and JAK2, approved for the treatment of patients with active rheumatoid arthritis. Because baricitinib, like other disease-modifying antirheumatic drugs, is used chronically, continuous assessment of its long-term safety profile is important. Here we provide updated data supporting the existing safety profile of baricitinib in this patient population. Methods: In this safety analysis, integrated data were included from nine phase 3, phase 2, and phase 1b clinical trials, and one long-term extension study with data up to 360 weeks, ending Feb 13, 2018. We analysed three integrated datasets, the largest of which was the all-bari-RA dataset, which includes patients who received any dose of baricitinib. We compared the safety of baricitinib with placebo on the basis of data from seven studies with baricitinib 4 mg and placebo and four studies with baricitinib 2 mg, including placebo to week 24 (placebo-controlled dataset). We did a dose-response assessment based on four studies with baricitinib 2 mg and 4 mg, including long-term extension data (2–4 mg extended dataset). We did an exploratory analysis of deaths and venous thromboembolic events in a subset of data from the all-bari-RA dataset that included patients who had ever taken baricitinib 2-mg or baricitinib 4-mg. We did an analysis for malignancies (excluding non-melanoma skin cancer) in the as-randomised population (patients not censored at rescue or dose change). Findings: We collected data for 3770 patients who were given baricitinib for 10 127 patient-years of exposure in the all-bari-RA dataset (median 1115 days [IQR 426–1441], maximum 2520 days). The placebo-controlled dataset comprised 2836 patients, with 1215 in the placebo group, with 451 patient-years of exposure data; 479 in the baricitinib 2 mg group, with 186 patient-years of exposure data; and 1142 in the baricitinib 4 mg group, with 472 patient-years of exposure data. The 2–4 mg extended dataset comprised 958 patients, with 479 in both the 2 mg and 4 mg groups. No significant differences were seen for baricitinib 4 mg or 2 mg versus placebo, or for 4 mg versus 2 mg in the incidence of death, malignancy, serious infection, or major adverse cardiovascular events. Incidence of herpes zoster per 100 patient-years was higher for baricitinib (4 mg: 4·4 [95% CI 2·7–6·7]; 2 mg: 3·1 [1·1–6·8]) versus total placebo group (1·1 [0·4–2·5]), as were treatment-emergent infections (4 mg: 89·7 [81·3–98·6]; 2 mg: 84·0 [71·3–98·2] vs placebo 75·4 [67·6–83·9]). Consistent with previous reports, incidences in the all-bari-RA dataset for venous thromboembolic events was 0·5 (95% CI 0·4–0·6) per 100 patient-years, deep-vein thrombosis was 0·3 (0·2–0·5) per 100 patient-years, and pulmonary embolism was 0·2 (0·2–0·4) per 100 patient-years. Incidences of malignancy (excluding non-melanoma skin cancer) in the 2–4 mg extended dataset were 0·8 (0·4–1·5) per 100 patient-years for baricitinib 2 mg and 1·0 (0·5–1·7) per 100 patient-years for baricitinib 4 mg, without censoring patients who had dose changes or received rescue treatment. We found no indication of higher incidence of venous thromboembolic events in the baricitinib 4 mg group compared with the 2 mg group in the 2–4 mg extended dataset. Interpretation: In this updated integrated analysis of patients with active rheumatoid arthritis exposed to baricitinib for a maximum of almost 7 years, baricitinib 2 mg and 4 mg maintained a similar safety profile to earlier analyses. No new safety signals were identified. Patients in the long-term extension study continue to be followed up to date. Funding: Eli Lilly and Company, under license from Incyte Corporation.